Incidencia de los tipos de Salmonella en los huevos de gallina criolla que se expenden en los mercados de Guaranda, Chimbo y San Miguel - Solano Buñay, Cristopher Santiago (2016)
In the city of Guaranda, Chimbo and San Miguel of the Province of Bolivar, located s an average altitude of 2668 meters above sea level, it was studied to determine the incidence of the types of Salmonella in eggs creole chicken which are sold in the markets of Guaranda, Chimbo and San Miguel. qualitative description statistical model was applied, 297 samples were analyzed on 99 eggs being analyzed both shell and contents (yolk - clear). numbers, percentages, means, frequencies and graphics were appointed. Planted research objectives were achieved in full: i) To establish the degree of incidence of Salmonella in eggs marketed Creoles. ii) Identify Salmonella serotypes. The methodology used were appropriate, using rigorously the steps of the scientific method. The experimental variables and results were adequate; 2% prevalence in shell eggs; 0% prevalence in white and yolk; Serotyping Salmonella enteritidis in shell; Origin Guaranda, San Miguel Chimbo and 100%; 0.67% incidence. The conclusions of the work are concise and illustrative, aimed at checking the initial hypothesis. Finally, this investigation found that the incidence of the types of Salmonella in eggs is low and creole chicken was related to disease control measures at the level of this food production, handling, transport and storage sites production and sale